The influence of methionine and vitamin E on oxidative stress in rats' liver exposed to sodium fluoride - Dominika Stolecka; Urszula Błaszczyk; Jolanta Zalejska-Fiolka; Ewa Romuk; Aleksander Owczarek; Ewa Birkner (Nofer Institute of Occupational Medicine, 2018)
Background Fluorine influences many processes occurring in the organism. Controversies over the evaluation of the biological effects of this substance are due to a small difference between tolerable and toxic fluorine doses. One of the main mechanisms of the fluorine toxic action is its ability to induce oxidative stress via reactive oxygen species generation and antioxidant defense system impairment. It is important to evaluate possible interactions between fluorine and other substances that may increase or decrease its toxicity. Material and Methods The study lasted for 35 days. Twenty-four rats were divided into 4 groups: the control, with sodium fluoride (NaF) in the diet, with sodium fluoride, methionine and vitamin E (NaF+M+E) in the diet, with sodium fluoride and vitamin E (NaF+E) in the diet. The biochemical analysis conducted in animal liver homogenates included determination of activities of: total superoxide dismutase (t-SOD), superoxide dismutase with copper and zinc (CuZnSOD), superoxide dismutase with manganese (MnSOD), glutathione peroxidase (GPX), catalase (CAT), glutathione reductase (GR), glutathione S-transferase (GST) and the malondialdehyde (MDA) concentration. Results The activities of CuZn- SOD, GPX, CAT and MDA concentration were changed significantly. There were no differences in the activities of t-SOD, MnSOD, GR and GST among the experiment. Conclusions In the conducted experiment, the run-out of enzymatic protection of liver by decreasing of the activities of antioxidant enzymes (CAT and GPX) and increasing the MDA concentration in NaF group was observed. The addition of vitamin E and methionine does not significantly stimulate the enzymatic antioxidant system, however, it causes of MDA concentration decreases. Med Pr 2018;69(4):403-412